Evaluation of low-temperature oxidation analysis and the development effect of high-pressure air injection in low-permeability reservoirs - Chen, Xinyu; Ba, Zhongchen; Lu, Zhiyuan; Gao, Yuhui; Zhou, Yang; Li, Xinrui (Frontiers in Earth Science, 2024)
In order to solve problems of conventional water injection development difficulties and low recovery factor in low permeability reservoirs, the method of highpressure air drive is adopted to achieve the purpose of reservoir energy enhancement and efficiency improvement. This paper conducted an experimental study on the mechanism of low-temperature oxidation (LTO) for crude oil in the process of highpressure air flooding, elaborated the relationship between the LTO properties of crude oil and the temperature, pressure, and water saturation of the reservoir, and analyzed the differences in LTO oxygen consumption and oil components under different reaction conditions. Besides, combined with the air flooding physical simulation experiment, the dynamic evolution law of recovery rate in the air flooding process was revealed. Findings from this inquiry indicate that an escalation in the oxidation temperature significantly amplifies the oxygen incorporation reaction within the crude oil matrix. This augmentation in oxidative conditions leads to an uptick in oxygen consumption, which subsequently precipitates a reduction in the lighter fractions of the oxidized oil, whilst enriching its heavier components. Elevated pressures were found to enhance the propensity for the amalgamation of unstable hydrocarbons with oxygen, fostering comprehensive and heterogeneous oxidation reactions. Notably, an excessive presence of water was observed to detrimentally affect the thermal efficacy of crude oil oxidation processes. In the context of low-permeability reservoirs, air injection techniques emerged as superior in effectuating oil displacement, albeit, an increase in injection pressures was associated with the phenomenon of gas channeling.Interestingly, adopting a sequential strategy of initiating with water flooding before air flooding facilitated the conveyance of high-pressure air via established flushing channels, though it appeared to attenuate the vigor of crude oil oxidation, culminating in an oil recovery efficiency apexing at 51%.